Corporate governance and firm innovation: Evidence from indigenous oil firms in Sub-Saharan Africa - Ekom Etim Akpan; Mamdouh Abdulaziz Saleh Al-Faryan; Jeremiah Favour Iromaka (Cogent Business & Management, 2022)
Previous studies on the effect of corporate governance on firm innovation shows mixed outcomes, while some reveal statistically significant effects, others show non-significant effects. Hence, this study aims at shedding more light on this unresolved phenomenon and fill this gap in literature by empirically examining the effect of corporate governance on firm innovation with special interest in indigenous oil firms in Nigeria, a Sub-Saharan country. The study adopted a cross sectional research design, while data were collected from respondents using a structured questionnaire and administered at a single period in time. Hypotheses were formulated for the study and tested using partial least square-structural equation modelling (PLS-SEM) through SmartPLS 3.2.9. The results demonstrated that corporate governance dimensions of board effectiveness, board commitment and board involvement have positive and statistically significant effects on firm innovation measures of process and product/service innovation. This study was limited to only indigenous oil firms in Nigeria, hence may not be generalized to other sectors of the economy. However, this study has far reaching implications to the industry. Most importantly, the study recommends ways to boost the level of innovation among indigenous oil firms which will enable them to remain competitive and sustainable. This study broadens literature on corporate governance and firm innovation especially in the Sub-Saharan African perspective. The study reveals that corporate governance through board effectiveness, commitment and involvement is essential for process and product/service innovation among indigenous oil firms.
Keywords: G34; N57; O31; 650; board commitment; board effectiveness; board involvement; Corporate governance; firm innovation; process innovation; product/service innovation